CAPITAL ADEQUACY RATIO PADA BANK YANG TERDAPAT DI BURSA EFEK INDONESIA (STUDI EMPIRIS TAHUN 2009 -2011) (Students' Journal of Accounting and Banking, 2014)
This study aimed to examine the effect of Non Performing loan, Net Interes Margin, Loan to deposit Ratio of the Capital Adequacy Ratio in banking companies in indonesia in 2009-2011.this meant that the banking companies in indonesia can make an optimal capital police strategi. So that the banking company may still exist for now and the future. There are several factors that influent in banking performance such as rentability and liquidity. There could be represented with its financial ratios which can predict banking performance on capital matter (Capital Adequacy Ratio). This research is performed in order to test the influence of the variable NPL, NIM, LDR, toward CAR. Sampling technique used is purposive sampling with criteria as General Banking in Indonesia who provide financial report and traded over period 2009 through 2011. The Data is based on publicity Indonesian Banking Directory since 2009 to 2011, that obtained by amount sample as much 81 company. Analysis technique used is doubled regression with smallest square equation and hypothesis test use t-statistic to test coefficient of regression partial and also f-statistic to test the truth of collectively influence in level of significance 5%. Other also done a classic assumption test covering normality test, multicollinierity test, heteroscedastisity test, and autocorrelation test. During research period show as data research was normally distributed. Based on multicollinierity test, heteroscedasticity test, and autocorrelation test variable digressing of classic assumption has not founded, which indicate that the available data has fulfill the condition to use multi linier regression model. The results showed that the variables NIM and LDR are partially significant effect to CAR, while LDR doesn’t have partially significant effect to CAR on State Owned Banks in Indonesia in 2003-2010 periods.Keywords: Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interst Margin (NIM), Loan to Deposite Ratio (LDR)